2015
DOI: 10.1152/ajplung.00043.2014
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase (MMP)-19-deficient fibroblasts display a profibrotic phenotype

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and usually lethal interstitial lung disease of unknown etiology characterized by aberrant activation of epithelial cells that induce the migration, proliferation and activation of fibroblasts. The resulting distinctive fibroblastic/ myofibroblastic foci are responsible for the excessive extracellular matrix (ECM) production and abnormal lung remodeling. We have recently found that matrix metalloproteinase 19 (MMP-19)-deficient (Mmp19Ϫ/Ϫ) mice develop an exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Supporting the notion that decreased autophagy activity contributes to fibrosis, we have found that knockout mice for MMP‐19, when exposed to bleomycin instillation, develop a stronger lung fibrotic response with the formation of fibroblasts foci. These fibroblasts exhibited a decrease in the expression of Atg4c, other member involved in autophagy stress response that has been associated with aging (Fernandez & Lopez‐Otin, ; Jara et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Supporting the notion that decreased autophagy activity contributes to fibrosis, we have found that knockout mice for MMP‐19, when exposed to bleomycin instillation, develop a stronger lung fibrotic response with the formation of fibroblasts foci. These fibroblasts exhibited a decrease in the expression of Atg4c, other member involved in autophagy stress response that has been associated with aging (Fernandez & Lopez‐Otin, ; Jara et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It was recently found that MMP‐19 deficient mice develop an exaggerated bleomycin‐induced lung fibrosis. These findings suggest that, in lung fibroblasts, MMP‐19 has strong regulatory effects on the synthesis of key extracellular matrix components, on fibroblast to myofibroblast differentiation, and on fibroblast migration and proliferation (Jara et al, ). Additionally, MMP‐19 has been discovered to be significantly upregulated in hyperplastic epithelial cells overlying fibroblast foci in IPF.…”
Section: Matrix Metalloproteinase‐19mentioning
confidence: 99%
“…Thus, in lung fibroblasts, MMP-19 has strong regulatory effects on the synthesis of key ECM components, on fibroblast to myofibroblast differentiation, and in migration and proliferation. 180 …”
Section: Special Attributes Of Specific Mmpsmentioning
confidence: 99%